Flow structure of the entrance of a T-junction duct without/with a circular cylinder. Issue 6 (3rd June 2019) - Wang, Xiaoyu; He, Jing; Su, Bo; Ke, Hanbing; Lin, Mei; Chen, Yitung
Abstract : The flow characteristics of the trailing edge of vertical vanes installed at the intersection of a T-junction duct were experimentally investigated using particle image velocimetry. The measured velocity field in the branch duct with/without single circular cylinder was studied under different cross velocities and velocity ratios. Additionally, the effect of the locations of cylinder on the flow field was discussed. The positive velocity region, the unsteady flow region and the trailing edge flow region of the vane, have been observed. The positive velocity region existed in almost one half of the measured area. As for the unsteady flow region, the unstable double-vortex structure transformed into a single-vortex structure as the velocity ratio increased. As for the trailing edge flow region of the vanes, the vortex streets could be visualised. Furthermore, the location of cylinder has revealed significant influence on the flow distributions in the trailing edge flow regions of the vanes. The flow structure without cylinder in the measured area is dependent on combinations of the cross velocity and velocity ratio, whereas that with cylinder is dependent on the velocity ratio. The vorticity fields were analysed in each region, and the velocity components revealed the cause of airflow trajectory.